Abstract - Redaktionen, - (Politica, 1990)
Torben Bech Dyrberg State and Civil Society - the Po!itica/ Constiution of the Social Order Jacob Torfing Gramsci and the neo-Gramscians: Towards a Societal Theory of the Primacy of Politics Uffe Østergård Clientelism as a Possible Form of the Postpolicical Society?